Analysis of Potential Hazards with Job Safety Analysis Techniques at Filling Stations and Transportation of Bulk LPG – PT. Tambang Yokodelta North Sulawesi - Arikalang, Aprillya; Adam, Arlin; Sanuddin, Sudirman; Zamli, Zamli (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: The LPG Bulk Filling and Transportation Station (SPPBE) at PT. Tambang Yokodelta Matungkas, North Minahasa, is a high-risk environment due to the flammable and pressurized nature of LPG. Identifying potential hazards is essential to ensure worker safety and prevent accidents. Objective: This study aims to analyze potential hazards and assess occupational risks using the Job Safety Analysis (JSA) method at the SPPBE of PT. Tambang Yokodelta. Methods: This qualitative research involved interviews and observations with eight informants, including the SPPBE manager, HSE head, technicians, and operators. Data were collected through interviews, field observations, and document review, and analyzed descriptively. Results: The study identified hazards classified into four risk levels: Low, Medium, High, and Extremely High. Low-risk activities, such as minor injuries, can be controlled with personal protective equipment (PPE). Medium risks, like falling during LPG handling, require additional PPE. High risks, including fire hazards during gas filling, need engineering controls. Extremely high-risk activities, such as gas explosions, require immediate management action and substitution measures. Conclusion: Workers at PT. Tambang Yokodelta face various risks. Effective control measures, including PPE, SOP compliance, engineering controls, and management commitment, are crucial for ensuring occupational safety.